European Union pharmacovigilance capabilities: potential for the new legislation. (August 2015) - Borg, John Joseph; Tanti, Amy; Kouvelas, Dimitrios; Lungu, Calin; Pirozynski, Michal; Serracino-Inglott, Anthony; Aislaitner, George
European Directives and Regulations introduced between late 2010 and 2012 have substantially overhauled pharmacovigilance processes across the European Union (EU). In this review, the implementation of the pharmacovigilance legislative framework by EU regulators is examined with the aim of mapping Directive 2010/84/EU and Regulation EC No. 1235/2010 against their aspired objectives of strengthening and rationalizing pharmacovigilance in the EU. A comprehensive review of the current state of affairs of the progress made by EU regulators is presented in this paper. Our review shows that intense efforts by regulators and industry to fulfil legislative obligations have resulted in major positive shifts in pharmacovigilance. Harmonized decision making, transparency in decision processes with patient involvement, information accessibility to the public, patient adverse drug reaction reporting, efforts in communication and enhanced cooperation between member states to maximize resource utilization and minimize duplication of efforts are observed.